Effects of polymorphisms in six candidate genes on phenytoin maintenance therapy in Han Chinese patients. (September 2012) - Hung, Chin-Chuan; Huang, Hsiao-Ching; Gao, Yun-Han; Chang, Wei-Lun; Ho, Jia-Ling; Chiou, Mu-Han; Hsieh, Yow-Wen; Liou, Horng-Huei
Aim: The present study aimed to investigate the associations between variants in pharmacokinetic- and pharmacodynamic-related genes with the dosages, concentrations and concentration–dose ratios (CDRs) of phenytoin (PHT).Methods & results: Eleven genetic polymorphisms in the six candidate genes were detected in 269 epileptic patients under maintenance PHT monotherapy by real-time PCR and PCR-RFLP. Results of a bivariate analysis demonstrated that among tested polymorphisms, carriers of the variant CYP2C9*3 tended to require significantly lower maintenance PHT dosages than wild-type carriers (p < 0.0001); on the other hand, carriers of the variants CYP2C9*3 or CYP2C19*3 revealed significantly higher CDRs than wild-type carriers (p < 0.004). In a further multivariate analysis, variants in SCN1A, CYP2C9, CYP2C19 and ABCB1 genes were significantly associated with CDRs of PHT under adjustment of age, gender and epilepsy classifications (adjusted r 2 = 20.07%).Conclusion: The results of present study indicated that polygenic analysis may provide useful information in PHT therapy optimization. Original submitted 3 May 2012; Revision submitted 28 June 2012